Sexual dimorphism in bite force in the grey mouse lemur. (24th February 2015) - Thomas, P.; Pouydebat, E.; Hardy, I.; Aujard, F.; Ross, C. F.; Herrel, A.
Abstract Sexual dimorphism is thought to be the result of sexual selection, food competition and/or niche differentiation, or simply the result of differential growth between the sexes. Despite the fact that sexual dimorphism is common among primates, lemurs are thought to be largely monomorphic. Yet, females of the species Microcebus are known to be larger than males. Here, we investigate if dimorphism in head dimensions is present in a colony of captive grey mouse lemurs Microcebus murinus. Moreover, we test whether any observed shape dimorphism is associated with differences in bite force between the sexes. Our results show that male and female grey mouse lemurs are indeed sexually dimorphic in head dimensions, with females having taller and wider heads than males. Moreover, we confirm previous observations that females are heavier than males. Bite force was principally determined by head dimensions and age in our dataset, and differed between sexes, with females biting harder than males. These data suggest a potential role for niche dimorphism in driving the observed shape and performance dimorphism as female reproductive output may depend upon the ability of animals to obtain resources that are difficult to ingest.